Tanggung Jawab Kantor Pertanahan Atas Perbuatan Melawan Hukum Dalam Kelalaian Pengukuran dan Pemetaan Batas Tanah - Tambunan, Enrico (Fakultas Hukum Universitas Airlangga, 2025)
Land has an important role in the lives of Indonesian people, where the majority of the population depends on land for their livelihoods, such as agriculture, housing, social activities and so on. The National Land Agency has the task of measuring land boundaries based on physical data and juridical data. The National Land Agency guarantees legal protection for land rights holders by issuing certificates as proof of legal protection, but in reality it does not guarantee legal protection because land disputes occur due to land boundaries being measured incorrectly and not being the same as in the field. The National Land Agency must be responsible for unlawful acts in negligence in measuring land boundaries, where the responsibility of the National Land Agency for negligence in measuring land boundaries is regulated in Minister of Agrarian Regulation No. 16 of 2016 concerning Amendments to Minister of Agrarian Regulation No. 24 of 1997 concerning Land Registration Article 41 paragraph (3), namely carrying out re-measurements of incorrect land boundary measurements and compensation for losses which are contained in the Civil Code Article 1365. This research is a research on the basis of the National Land Agency's responsibility for unlawful acts in negligence in measuring land boundaries. Conclusion The National Land Agency is responsible for negligence that causes losses where the act of negligence is an act against the law. Key words: National Land Agency; Act against the law; Land Boundary Measurement.